THE STRATEGIC ROLES OF PUBLIC RELATIONS DURING COVID-19 CRISIS IN GOVERNMENT ORGANIZATION - Albert, Alif Syafik; Ridzuan, Abdul Rauf; Djuyandi, Yusa (Aliansi, 2024)
In our current era of global interconnectivity, the significance of public relations (PR) in crisis management has become increasingly crucial. Government organization often face crises that demand prompt and strategic communication to minimize harm and uphold stakeholders trust. This study aims to examine the strategic roles of public relations in crisis scenarios by analyzing pertinent case studies, theoretical frameworks, and empirical data. The study utilized a systematic review methods, specifically examining publications both from quantitative and qualitative research published on Google Scholar from 2021 to 2024. The study focused on the following keywords: crisis management, public relations, communication strategy, and organizational reputation. Following the screening process, fourteen studies satisfied the criteria specified for this research. The results suggested that successful public relations strategies during times of crisis require prompt communication, openness, and proactive involvement with individuals or groups having a vested interest in the situation. This study enhanced comprehension of the crucial function of public relations in crisis management and provides practical insights for both public relations professionals and researchers. Subsequent investigations should delve into the changing dynamics of public relations in the era of digital technology and analyze its consequences for crisis management tactics.